Latent tuberculosis infection among patients with erectile dysfunction. Issue 1 (February 2018) - Hasanain, Ahmad; Mahran, Ali; Safwat, Ahmed; Nafee, Amany; Zayed, Ali; Abdel-Aal, Sherif; Bakkar, Sally; Abonnoor, Ahmad
Abstract No previous studies have investigated the prevalence of latent tuberculosis infection (LTBI) among patients with erectile dysfunction (ED) or its contribution to the development of high-grade ED through a process of chronic inflammation-induced atherosclerosis. The aim of this study was to determine the frequency of LTBI among patients with erectile dysfunction and to explore the contribution of LTBI to high-grade ED. For all the study sample, clinical evaluation, imaging studies, and laboratory investigations were provided. Evaluation included, but was not confined to, scrotal ultrasonography, tuberculin skin test, and QuantiFERON-TB Gold test. The study sample mean ± SD age was 47.9 ± 13.6 years. Approximately 30% of the patients had LTBI and 43% had high-grade ED. After a multivariate analysis, it was found that older age (≥40 years) (OR, 5.2; 95% CI, 1.9–54.6;p 0.004), metabolic syndrome (MS) (OR, 3.4; 95% CI, 1.3–48.2;p 0.016), and LTBI (OR, 4.1; 95% CI, 1.7–61.3;p 0.021) were significantly, independently associated with high-grade ED as opposed to low-grade ED. In conclusion, the prevalence of LTBI among patients with high-grade ED is higher than among those with low-grade ED. In addition to LTBI, older age and MS are associated with high-grade ED as opposed to low-grade ED.